Real‐Time Metrology for Roll‐To‐Roll and Advanced Inline Manufacturing: A Review. Issue 2 (20th November 2022) - Maize, Kerry; Mi, Ye; Cakmak, Miko; Shakouri, Ali
Abstract: Roll‐to‐Roll (R2R) manufacturing is changing how state‐of‐the‐art technology is made. Roll‐to‐Roll is part of a family of advanced scalable inline manufacturing techniques that make traditional and state‐of‐the‐art products at high yield and reduced cost. R2R manufacturing has grown rapidly and is fundamental to several advanced technologies such as functional materials and films, sensors for medicine, biology, and environment monitoring, energy harvesting devices, and flexible electronics. Advantages of R2R manufacturing include ease of machine design, adaptability to a wide range of additive processing methods, and very high throughput. To keep up with advances in R2R manufacturing, novel methods have emerged to measure important product metrics (thickness, roughness, conductivity) and monitor quality (uniformity, defects) inline and in real‐time. This review provides an overview of the state‐of‐the‐art for real‐time inline metrology and quality control in modern R2R manufacturing. The survey considers both established inline metrology techniques such as line‐scan imaging and reflectometry, and techniques recently adapted or that show promise for real‐time inline R2R metrology such as ellipsometry, hyper‐spectral imaging, and Raman spectroscopy. Abstract : Roll‐to‐Roll (R2R) manufacturing promises scalable and affordable production of critical emerging technologies. Next‐generation R2R will require advanced quality control techniques that monitor processing and products inline in real‐time. This review explores state‐of‐the‐art real‐time, inline metrology for R2R manufacturing. The broad survey discusses traditional techniques, recent innovations, and well‐established offline measurement techniques that show promise for inline R2R metrology.